2023
DOI: 10.1186/s12974-023-02836-4
|View full text |Cite
|
Sign up to set email alerts
|

CD200 in dentate gyrus improves depressive-like behaviors of mice through enhancing hippocampal neurogenesis via alleviation of microglia hyperactivation

Abstract: Background Neuroinflammation and microglia play critical roles in the development of depression. Cluster of differentiation 200 (CD200) is an anti-inflammatory glycoprotein that is mainly expressed in neurons, and its receptor CD200R1 is primarily in microglia. Although the CD200–CD200R1 pathway is necessary for microglial activation, its role in the pathophysiology of depression remains unknown. Methods The chronic social defeat stress (CSDS) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“… 30 In addition, the plasticity of neurons in the hippocampus is high, which is closely related to memory, emotion, and learning function. 31 , 32 Studies have shown that stress can affect the activation of microglia in the hippocampus, which in turn increases the expression of TNF-α in the tissue 33 At the same time, hippocampal CD38 is closely related to depression-like behavior in the inflammatory model. 34 In short, the hippocampus is one of the most studied brain regions in animal models of depression, and it is also considered to be the brain region that is most closely related to depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 In addition, the plasticity of neurons in the hippocampus is high, which is closely related to memory, emotion, and learning function. 31 , 32 Studies have shown that stress can affect the activation of microglia in the hippocampus, which in turn increases the expression of TNF-α in the tissue 33 At the same time, hippocampal CD38 is closely related to depression-like behavior in the inflammatory model. 34 In short, the hippocampus is one of the most studied brain regions in animal models of depression, and it is also considered to be the brain region that is most closely related to depression.…”
Section: Discussionmentioning
confidence: 99%
“…30 In addition, the plasticity of neurons in the hippocampus is high, which is closely related to memory, emotion, and learning function. 31,32 Studies have shown that stress can affect the activation of https://doi.org/10.2147/NDT.S445636…”
Section: Discussionmentioning
confidence: 99%
“…Considering that mice deficient in CX3CR1 have impaired neurogenesis and synaptic plasticity, reduced expression of this chemokine could negatively affect neuroplasticity pathways [ 105 ]. Interestingly, the neuronal glycoprotein cluster of differentiation 200 (CD200) acts in a similar way to CX3CL1 by activating the microglial CD200R1 receptor [ 106 , 107 ]. In a chronic stress model induced by social defeat, the induction of depressive-like behaviors was related to microglial activation and a decrease in CD200 in the hippocampal dentate gyrus.…”
Section: Neuroinflammation: Function Of Glial Cellsmentioning
confidence: 99%
“…In a chronic stress model induced by social defeat, the induction of depressive-like behaviors was related to microglial activation and a decrease in CD200 in the hippocampal dentate gyrus. In contrast, exogenous CD200 treatment alleviated the neuroinflammatory response and increased BDNF expression, which in turn improved hippocampal neurogenesis in this model [ 107 ]. These findings suggest that microglial activation is one of the possible mechanisms underlying the impaired neuroplasticity seen in MDD [ 77 ].…”
Section: Neuroinflammation: Function Of Glial Cellsmentioning
confidence: 99%
“…Stress-induced abnormal activation of microglia can impair the physiological process of neurogenesis, thereby leading to depression-like behavior. Reducing excessive neuroinflammation can ameliorate impaired neurogenesis and serve as a treatment for depression ( Amanollahi et al, 2023 ; Chen et al, 2023 ).…”
Section: Pathological Connection Between Ahn and Mddmentioning
confidence: 99%